Fruit yield and growth parameters of several Carica papaya L. genotypes in a temperate climate - Céccoli, Gabriel; Panigo, Elisa Soledad; Gariglio, Norberto; Favaro, Juan Carlos; Bouzo, Carlos Alberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The aim of this work was to evaluate changes in growth and productivity parameters of different precocious hybrids and a naturalized variety of papaya under both greenhouse and field cultivation in a temperate climate (the center of the province of Santa Fe, Argentina). In view of the aforesaid, the purpose of our research was to identify further genotypes better suited for the cultivation of this species in temperate climates and demonstrate the need for the use of semi-controlled systems to make possible the cultivation of these promising genotypes in middle latitudes. The average yield was 291% higher in greenhouse than in the field. The average productivity for hybrid genotypes compared with the naturalized variety more than doubled in both environments. Considering behavior in height, leaf area index and yield parameters, hybrids H2 (principally), and H4 showed a great adaptation for use in semi-forced systems. The use of greenhouse and short stature papaya hybrids allows its feasible and surely profitable cultivation in non- tropical climates.